Desempenho, características de carcaça e avaliação Morfológica de tourinhos sindi mantidos em pasto - Paiva, Celso Carlos Pinheiro Lamartine (Universidade Federal Rural do Semi-Árido, 2018)
The weight gain tests conducted entirely on pasture evaluate the individual performance of the animals, providing selection subsidies based on individual phenotypic information. The objective of this study was to evaluate the performance, ultrasonic characteristics of the caraway and the morphology of 20 pure Sindi bulls kept under pasture during official weight gain test conducted by the Brazilian Association of Zebu Breeders (ABCZ). For 294 days, of which 70 were adapted for adaptation, the animals were kept in pasture formed by Brachiaria grass (Urochloa brizantha), Pangola (Digitaria decumbens), Tifton (Cynodon sp.) and Massai (Panicum maximum cv. Massai), using the rotational stocking method, with periods of occupation of 20 days. Weights and measurements of scrotal circumference occurred every 56 days. Ultrasonographic evaluation of the carcass and visual morphological evaluation occurred on the day of the last weighing. Data were submitted to descriptive analysis, simple linear correlation and mean test. The final weight, mean daily gain and gain in scrotal circumference were 304.60 ± 39.13 kg, 0.482 ± 0.09 kg / day and 10.29 ± 2.13 cm, respectively. In relation to the ultrasound evaluation of the carcass, a mean of 52.36 ± 7.01 cm² was found for loin-eye area, 1.25 ± 0.63% intramuscular fat and, for the loin fat thickness and of picanha, 1.26 ± 1.23 and 2.60 ±, 84 mm, respectively. The total of points for visual morphological evaluation was 24.75 ± 2.02. There was a significant positive and moderate correlation between EGP and EGL; EGL and P; P and M; S and E. For the parameters of performance, AOL and visual evaluation (EPMURAS), there was a positive and significant correlation between the following parameters: GMD and GPT; PN and PI; PN and FP; CEini and CEf; AOL and PF; PI and E; PF and E; PN and A; P and A; and CEf and S. There was no effect (P> 0.05) of the initial weight on carcass characteristics, performance parameters and visual evaluation. The results of the first weight gain test conducted in Brazil show the hardiness of the Sindi breed, the high gain compensation capacity of these animals and the breed fitness for meat production, verified by the ultrasound evaluation of the carcass. The Pearson correlation coefficients established between the performance parameters, the carcass characteristics and the visual morphological evaluation prove the accuracy of this type of evaluation made by ABCZ technicians
Keywords: Avaliação visual; Bovinocultura de corte; Espessura de gordura; Marmoreio; Precocidade; Visual evaluation; Cattle breeding; Thickness of fat; Marbiling; Precocity; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL